# algebra

posted by .

how would I solve it since they are not together?

• algebra -

These simultaneous equations can be solved most of the time by either substitution or by elimination. We will try elimination here, since I see 5y in both equations.

3x-5y=-2....(1)
5y-2x=-2....(2)
Rearrange to line up x and y in columns
3x-5y=-2...(1a)
-2x+5y=-2...(2a)
3x-2x -5y+5y = -2 -2
simplify to get
x = -4 ... (3)

Substitute (3) into (1) to get
3(-4)-5y=-2
-5y = -2 + 12
-5y = 10
y = 10 / (-5) = -2 ..(4)

(3) and (4) give the final answer, but we still have one more step to do: check!

Substitute (3) and (4) into (1) and (2) to get
3(-4)-5(-2)
=-12+10
=-2 from (1) OK

5(-2)-2(-4)
=-10+8
=-2 from (2) OK

## Similar Questions

1. ### Algebra 2345678!!

Solve the system of equations using the Addition method. 2a + 3b = -1 3a + 5b = -2 The addition method tells you to find common multiples of a coefficient, then add the equations together to eliminate a variable. If you multiply the …
2. ### math ALGEBRA

Solve by either the substitution method or the addition or subtraction method 2m=n-3 3m=2n-9 Just replace n with (2m + 3) in the second equation. Then solve for m. Once you know the value of m, use either of your equations, such as …
3. ### bartlett hill,math

add the like terms together.a+b+a+2b Okay. Well, the questoin says to add the like terms together, that means add the A's together and add the B's together. a+b+a+2b Alright, so your a's and your first b don't have a number in front …
4. ### algebra-need quick

solve the system by addition method 7x^2+y^2=49 7x^2-y^2=49
5. ### algebra- help needed fast

solve the system by addition method 7x^2+y^2=49 7x^2-y^2=49
6. ### Algebra.

Solve using the addition and mulitplication method principles. 4+9x<13. Is this right?
7. ### algebra 2

Solve the system by the addition method x+3y=-2 5x+15y=-10
8. ### MaTh = Algebra = help

Solve this system of linear equaiton by an algebraic method. So If I had to solve this the elimination method way, how would I do it?
9. ### algebra

solve by addition method x +3y +z =6 3x + y – z = -2 2x +2y – z = 1 thanks
10. ### algebra

solve by addition method x +3y +z =6 3x + y – z = -2 2x +2y – z = 1

More Similar Questions